2014
DOI: 10.1155/2014/982150
|View full text |Cite
|
Sign up to set email alerts
|

Antineutrophil Cytoplasmic Antibody Frequency in Chronic Hepatitis B Patients

Abstract: Background. Chronic hepatitis B (CHB) is a viral disease, common across the world, and associated with several extraintestinal manifestations including vasculitis. Antineutrophil cytoplasmic antibodies (ANCAs) are sensitive and specific markers for vasculitides. There is limited data available in the literature on whether ANCA formation is stimulated by CHB infection. In the present study we aimed to identify the frequency of ANCA in CHB patients. Methods. A total of 174 subjects were included in the study (87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Ghonaim et al developed a study of chronic viral hepatitis patients and showed higher frequency of ANCA in chronic HCV infection than in the group control, but the same was not observed in chronic HBV group. However, in a study performed by Calhan et al, the frequency of ANCA was higher in chronic HBV patients in comparison with healthy controls [11]. HBV is associated with several extrahepatic manifestations such as vasculitis [11,12] due to deposition of immune complexes [12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Ghonaim et al developed a study of chronic viral hepatitis patients and showed higher frequency of ANCA in chronic HCV infection than in the group control, but the same was not observed in chronic HBV group. However, in a study performed by Calhan et al, the frequency of ANCA was higher in chronic HBV patients in comparison with healthy controls [11]. HBV is associated with several extrahepatic manifestations such as vasculitis [11,12] due to deposition of immune complexes [12].…”
Section: Discussionmentioning
confidence: 90%
“…However, in a study performed by Calhan et al, the frequency of ANCA was higher in chronic HBV patients in comparison with healthy controls [11]. HBV is associated with several extrahepatic manifestations such as vasculitis [11,12] due to deposition of immune complexes [12]. The causal relationship between chronic HBV infection and polyarteritis nodosa was the only well established in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Although the presence of serum ANCA has proven useful for the diagnosis of ANCA-associated vasculitis in appropriate clinical setting, it is often elevated in a non-specific manner (13). In previous studies for hepatitis virus infection, the frequency of ANCA was not low in patients with HBV and hepatitis C virus (HCV) infection, and some patients with hepatitis virus infection demonstrated ANCA-associated vasculitis (3,14,15). The pathogenesis of hepatitis virus triggering autoantibodies or autoimmune disease, such as ANCA or ANCA-associated vasculitis, remains unknown.…”
Section: Discussionmentioning
confidence: 96%
“…A significant number of patients with transverse myelitis have been found to be p-ANCA and c-ANCA positive, albeit these cases were idiopathic [10]. Moreover, borderline positive c-ANCA was significantly higher in chronic hepatitis B group as compared to control [2]. …”
Section: Discussionmentioning
confidence: 99%
“…It is associated with several extrahepatic manifestations including but not limited to serum sickness, polyarteritis nodosa, urticaria, leukocytoclastic vasculitis, and essential mixed cryoglobulinemia. In addition to these manifestations, hepatitis B virus (HBV) has also been documented to be involved in the etiopathogenesis of antineutrophil cytoplasmic antibodies (ANCA)-positive vasculitis [2]. …”
Section: Introductionmentioning
confidence: 99%